Geology of the Tabakoto gold deposit, Kédougou-Kéniéba Inlier, West African Craton, Mali - Diallo Mahamadou; Salvi Stefano; Baratoux Lenka; Béziat Didier; Vanderhaeghe Olivier; Labou Ibrahima; Baratoux David; Ly Saïdou (BSGF - Earth Sciences Bulletin, 2024)
The Tabakoto gold deposit is part of the highly endowed west-Malian gold belt, which hosts several world-class deposits. Located in the Paleoproterozoic Kédougou-Kéniéba Inlier (KKI) of the West African Craton (WAC), the deposit is contained in Birimian metasedimentary rocks of the Kofi series that are intruded by magmatic dikes. The Tabakoto deposit is characterized by multiple overlapping stages of magmatic dike intrusions and hydrothermal alteration during distinct regional-scale deformation events. The metasedimentary rocks are characterized by a S0/1 foliation delineated by the alternation of metagreywacke and meta-argillite. This foliation is affected by upright folds with N-S trending axial planes marked by a S2 schistosity and cross-cut by conjugate steep-dipping dextral NE-SW and sinistral NW-SE trending faults. These structures record regional-scale E-W shortening, first associated with crustal thickening and then with N-S stretching, evolving from ductile to brittle deformation. The gold-bearing V2 quartz-pyrite veins developed in dikes and metasedimentary units, are parallel to the S2 schistosity of the DT2 deformation event. These veins contained reduced phases such as pyrrhotite, loellingite and scheelite as well as bismuth. The second gold-bearing V3a quartz-carbonate veins are located in the NE-SW and NW-SE trending faults of the DT3 deformation event. The latter veins are marked by sodic alteration followed by carbonate (i.e., dolomite-ankerite ± calcite ± siderite) and phyllic (i.e., chlorite-muscovite-sericite) alterations. In the quartz-pyrite veins, gold occurs as inclusions in pyrite, arsenopyrite, and pyrrhotite, whereas in quartz-carbonate shear veins, gold is present in microfractures cross-cutting pyrite and arsenopyrite and at the contact between grains of pyrite and arsenopyrite, and of arsenopyrite and pyrrhotite. The litho-structural and mineralogical features of the Tabakoto deposit portray a polyphase mineralization with (i) an intrusion-hosted orogenic gold system, where the metabasltic to metarhyolitic dikes acted as suitable emplacement for fluids flow and (ii) a hydrothermal fluid circulation under ductile to brittle conditions.